Upaya Peningkatan Kemampuan Komunikasi Matematis dan Kecerdasan InterpesonalDengan Penggunaan Pembelajaran Tutor Sebaya di SMK N 2 Medan - Rennika I.S. Simorangkir; Dwi Novita Sari; Desniarti Desniarti; Seprianti Harahap; Risna Ula Siregar (Departement of Mathematics Education, 2024)
This study is a form of classroom action research (CAR) consisting of two cycles. The process comprises four stages: planning, implementation, observation, and reflection. The objective of this classroom action research is to assess the enhancement of students' mathematical communication abilities and interpersonal intelligence through the implementation of the peer tutoring cooperative learning paradigm. The study included a sample of 30 students from Class XI in the Machining Engineering Department at SMK Negeri 2 Medan. The data collection methods employed encompassed observation, questionnaires, and tests. The study's findings demonstrated enhanced mathematical communication abilities and interpersonal intelligence among the pupils. Evidence of this can be observed in the notable improvement of students' mathematical communication skills and interpersonal intelligence. Specifically, there was a significant rise in written mathematical communication skills from 20% to 66.6%, and a substantial increase in students' interpersonal intelligence from 43.3% to 86.6%. The findings suggest that the adoption of the peer tutoring cooperative learning model is successful in improving students' proficiency in mathematical communication and interpersonal intelligence at SMK Negeri 2 Medan. Enhancing mathematical communication skills and interpersonal intelligence within an educational environment can contribute to the overall objective of training students to be proficient and capable professionals in real-world situations.